Dearabization of Islamic Government during the Abbasid Dynasty - Riyadi, Ahmad Syafi'i Mufadzilah; Putra, Muhammad Habib Adi (Journal of Islamic History and Manuscript, 2022)
The Arabization movement was one of the government's political models during the Umayyad Dynasty. Arabization, known as ta'rib became a characteristic of the administration of the Umayyad dynasty, which influenced the socio-political life of Arab Muslims, the Mawali, and Dzimmi groups. The influence of social strata became a feature of the Arabization movement at that time. During the Abbasid dynasty, this movement began to fade, especially the problem of social strata that prioritized Arab Muslims. The Abbasid dynasty, from the point of view of Islamic civilization, generally continued the reign of the Umayyad dynasty, but some aspects of government changed, especially the issue of Arabization. This study focuses more on the impact of the reduced priority of Arab Muslims during the Abbasid dynasty. The demise of the Abbasid dynasty gave a new face to the development of politics, economy, government administration, education, and law enforcement aspects. This research is a type of qualitative research using qualitative descriptive analysis. This type of research is historical research with a socio-political approach to government. The qualitative method used in this study uses historical research methodology, namely heuristics, verification, interpretation, and historiography. Based on the heuristic aspect, the researcher used a literature study. The results of this study indicate that the existence of Dearabization had a significant impact on the reign of the Abbasid dynasty. The policies taken by the caliphs of the Abbasid dynasty gave a new color to the development of politics, economy, government administration, education, and law.